Giant Rhabdomyosarcoma in A Child: A Rare Entity - Sharma, Gopal Raman; Joshi, Sumit; KC, Raj Kumar; Bhattachan, Maya (Nepal Journal of Neuroscience, 2018)
Rhabdomyosarcoma (RMS) is a highly aggressive and rapidly progressive sarcoma. RMS can occur in any part of the human body, however, paraspinal or paravertebral or epidural RMS is very rare in children. We present a case report of 3 year old male child with right paraspinalRMS with intracanalicular extension at L3– S1 level, presented with painful swelling at lower back region. We will review the literature and discuss on epidemiology, diagnosis, management strategy and prognosis of RMS.Nepal Journal of Neuroscience 15:35-37, 2018